Breach of traveller privacy in location-based social media. Issue 15 (14th September 2019) - Vu, Huy Quan; Law, Rob; Li, Gang
ABSTRACT: The availability of location-based social media (LBSM) presents various opportunities for tourism researchers and businesses to understand and enhance the traveller experience. However, privacy concerns can prevent users from sharing their location data, impeding the future development of LBSM applications. Privacy issues of LBSM remain under investigation in the tourism literature probably because social media platforms are often assumed to feature good security mechanisms. This paper argues that risks of privacy disclosure exist not from direct access to private data but indirectly through seemingly harmless data published by users. We present a social link mining technique and demonstrate how private and sensitive information in the form of social relationships between travellers can be revealed. The ﬁndings can support managers and researchers in realizing the potential privacy risks of LBSM so that effective strategies can be developed to protect users and promote the gains that LBSM can bring.